Analisis Faktor-faktor Yang Mempengaruhi Tingkat Investasi Kabupaten/Kota di Kalimantan Barat Tahun 2009-2013â€ - B01111023, MUHAMMAD NAJIB NAJIB (Jurnal Pembangunan dan Pemerataan, 2015)
Investment plays important roles in the economic structure in West Kalimantan Province. One of them is to help accelerate the growth of regional development which has not been developed by government. Seeing the importance of such investment in the economy, government needs to improve every aspect in governance, such as the allocation of local government expenditure as well as per capita income to attract both internationaal and national investments.This study aimed to analyze the influence variables, government expenditure, and per capita income by analyzing variables which impact the most on investment level in regencies/cities in West Kalimantan Province from 2009 to 2013. The research method used was explanatory research method and the analysis method was multiple regression analysis using panel data that combines the data time series with cross section from 2009 to 2013. There were 12 regencies/cities in West Kalimantan Province as the data of the study processed in multiple regression models with 36 observations.The result of multiple regression analysis showed that the variable of government expenditure (G) significantly gives an impact on the level of investment while per capita income (PP) has no significant effect on the level of investment. Meanwhile, government income and per capita income, if assesed jointly, affect on the level of investment positively and significantly in the regencies and cities in West Kalimantan Province. This shows that government in the regencies/cities in West Kalimantan Province.Keywords: Level of investment, government expenditure and percapita income.